Oxygen allows Shewanella oneidensis MR-1 to overcome mediator washout in a continuously fed bioelectrochemical system - TerAvest, Michaela A.; Rosenbaum, Miriam A.; Kotloski, Nicholas J.; Gralnick, Jeffrey A.; Angenent, Largus T. (Biotechnology and bioengineering, 2014)
ABSTRACT Many bioelectrochemical systems (BESs) harness the ability of electrode‐active microbes to catalyze reactions between electrodes and chemicals, often to perform useful functions such as wastewater treatment, fuel production, and biosensing. A microbial fuel cell (MFC) is one type of BES, which generates electric power through microbial respiration with an anode as the electron acceptor, and typically with oxygen reduction at the cathode to provide the terminal electron acceptor. Oxygen intrusion into MFCs is typically viewed as detrimental because it competes with anodes for electrons and lowers the coulombic efficiency. However, recent evidence suggests that it does not necessarily lead to lower performances—particularly for the model organism Shewanella oneidensis MR‐1. Because flavin‐mediated electron transfer is important for Shewanella species, which can produce this electron shuttle endogenuously, we investigated the role of flavins in the performance of pure‐culture BESs with S. oneidensis MR‐1 with and without oxygen. We found that oxygen increases current production more than twofold under continuously fed conditions, but only modestly increases current production under batch‐fed conditions. We hypothesized that oxygen is more beneficial under continuously fed conditions because it allows S. oneidensis to grow and produce flavins at a faster rate, and thus lowers flavin washout. Our conclusions were supported by experiments with a flavin‐secretion deficient mutant of S. oneidensis. Biotechnol. Biotechnol. Bioeng. 2014;111: 692–699. © 2013 Wiley Periodicals, Inc. The authors investigated the importance of flavins—endogenous electron mediators—in electron transfer between Shewanella oneidensis MR‐1 and anode electrodes under anaerobic and micro‐aerobic conditions. Micro‐aerobic conditions promoted mediated electron transfer via flavins under continuously fed conditions, but had little effect on the electron transfer mechanism under batch‐fed conditions. This indicates that oxygen allowed S. oneidensis to overcome flavin washout in the continuously fed condition, either by increasing cell mass or by increasing per cell flavin production. This result may have broader implications for both mixed‐ and pure‐culture bioelectrochemical systems harboring aerotolerant organisms.